N2O as a dynamical tracer in the Arctic vortex - Loewenstein, M.; Podolske, J. R.; Chan, K. R.; Strahan, S. E. (1990)
This paper reports N2O measurements obtained by the Airborne Tunable Laser Absorption Spectrometer from 14 flights of the NASA ER-2 aircraft during the 1989 Airborne Arctic Stratospheric Expedition field campaign. In the altitude range expected for ozone loss, N2O has a long photochemical lifetime, making it an excellent tracer of lower stratospheric air motions. As in the southern hemisphere, the zonal wind speed maximum and large gradients of potential vorticity and N2O identify the vortex edge. The N2O profiles inside the vortex indicate net descent relative to outside the vortex and to the summer polar lower stratosphere. The descent of the N2O profile during the Arctic night relative to the summer profile is comparable to the downward shift in the vertical profile observed in the 1987 Antarctic winter vortex. Winter profiles at the poles are very similar above the 435 K potential temperature surface, but divergent below.